Effect of body size on microhabitat preferences in stream‐dwelling fishes. (April 2017) - Manna, L. R.; Rezende, C. F.; Mazzoni, R.
Summary: Microhabitat preferences of two stream‐dwelling fish assemblages in two different Brazilian habitats of rainforest and semi‐arid vegetation and comparisons within and between species were investigated. Data collection was from June to October 2012 in the Gato Stream within the rainforest, and from April to September 2012 in the Curu Stream within a semi‐arid vegetation. Snorkeling observations and diving sessions along a 200‐m stretch in each stream were performed. In total, 39 diving sessions were made over a total of 55 hr of underwater observations. Microhabitat preferences of the fish were analyzed by comparing resource use by fish species to the resource availability of the streams. Use of the microhabitat differed significantly between fish species within and between assemblages. In addition, there was a higher level of intraspecific variation in the fish assemblage in the semi‐arid area. There was no significant correlation between fish size and microhabitat use, but five species showed a significant correlation between microhabitat use and distance from the stream bank. The findings herein point to highly intraspecific variability in both fish assemblages and highlight the importance of measuring individual differences in microhabitat preferences. Additionally, the versatility described for tropical freshwater fishes confirms the importance of measuring the intraspecific variability of their different ecological traits, and challenges the use of morphology as a predictor of fish ecology.